Investigation of a hybrid system with ground source heat pump and solar collectors: Charging of thermal storages and space heating. (March 2020) - Georgiev, Aleksandar; Popov, Rumen; Toshkov, Emil
Abstract: A hybrid installation that includes solar collectors and a ground source heat pump was developed and tested. There are many studies in the field of combined heat pump systems describing relatively large installations, designed for climatic conditions and soil thermal properties different from those in Bulgaria, where the experimental data are limited. The paper presents the construction of a small size hybrid installation containing diurnal and seasonal storages and supporting five different modes of operation with emphasis on the charging of borehole heat exchanger (BHE), heating mode with ground source heat pump (GSHP) and the followed natural relaxation. The paper also proposes a methodology for determination of different system energy efficiencies. High quality data for the different system operation modes in terms of soil and weather conditions typical of the Plovdiv region were obtained. The study proves the necessity of BHE charging with thermal energy from the sun during the summer mainly to avoid the ground thermal depletion. The comparison of the three heating modes investigated shows evident advantage of the ground source heat pump heating (GSHPH). The installation must be tested in the future for a longer time period. Highlights: Hybrid system with solar collectors & ground source heat pump was created and tested. Methodology for calculation of different system energy efficiencies was created. It is accentuated on BHE charging, GSHP heating mode and followed natural relaxation. Precise realization of TRT and 5 operation modes resulted in detailed energy diagrams. GSHPH mode (efficiency of 96.46%) has higher potential compared with the other modes.